Design Of Outpatient Medical Record Information System At Hermina General Hospital Serpong Using Web-Based Prototype Method - Izzuddin, Muhammad Ayom (STEBIS Bina Mandiri, 2025)
The design of the Outpatient Medical Record Information System at Hermina Serpong General Hospital using a web-based prototype method aims to develop an effective and efficient system in managing outpatient medical records. Currently, the management of medical records at Hermina Serpong General Hospital is still done manually, which can cause difficulties in searching for patient data, potential recording errors, and suboptimal services. Therefore, a system is needed that can improve the quality of health services, speed up the administration process, and reduce the risk of data errors. The prototype method was chosen in designing this system because it allows faster and more flexible development, involving feedback from users to produce a system that suits the needs. The system is designed web-based, allowing easy and fast access to information through devices connected to the internet, thus increasing ease of use and accelerating the flow of information. The result of this study is an outpatient medical record information system that can manage patient data, examination history, diagnosis, treatment, and visit schedules, which can be accessed by medical personnel, administration, and other related parties. With this system, it is expected to improve data accuracy, time efficiency, and the quality of medical services for patients at Hermina Serpong General Hospital.